Ti-modified Clay Composite for Removal of Highly Toxic Chromium Compounds from Polluted Water by the Means of Adsorption - Doroshenko, Alisa; Gorodylova, Nataliia Oleksandrivna; Herbert, J.; Šulcová, Petra (Česká společnost průmyslové chemie, 2016)
In the current work, 12 different Ti-modified clay composites were synthesised. XRD analysis and surface area measurements have been used to investigate the samples. The influence of the synthesis approach and adsorption experiment parameters on the final adsorption values of dangerous carcinogen Cr (VI) were investigated in concentration range from 2 mg/L to 42 mg/L with pH 4 and 6. In the result of the work the efficiency of carcinogen hexavalent chromium removing can be up to 98,5 % depending on the conditions.
Ti-modifikovaný jílový kompozit pro odstranění vysoce toxických sloučenin chrómu ze znečištěné vody pomocí adsorpce
Keywords: Ti-modifed clay; XRD analysis; Cr(VI); Adsorption; Ti-modifikovaný jíl; RDX analýza; Cr(VI); adsorpce